Intensifications reactive power during of asymmetric network outages in dual-stator winding generators - Qasim Al Azze; Balasim М. Hussein; Hayder Salim Hameed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The paper proposes a protection to dual stator generator, reluctance rotor, from asymmetrical fault. Which prevents the dual stator generator, reluctance rotor, from electrical sage through working process in order to avoid any interruption in the generator-grid connection. The procedure consummated with injecting suitable reactive power during the fault period. The proposed method that makes it possible for wind turbine application via dual stator winding generators (DSWRG) synchronous mod to stay connected to the grid during asymmetrical faults. It has been built according to trusted simulating mode considering all tested parameters according to experiment work. The expirment, consider the DC link side stability and care about the behavior and performance of machine side parameter. As well the machineability is evaluated to ride through asymmetrical fault by observing the secondary side current which has a big role in saving grid side converter. The control takes a response within 200 ms after fault trigger recognition. The generator ability of dynamically remaining connected stable and existing in the network, which is sustained a series voltage disturbance by injecting appropriate amount of reactive power. The main interest required in this paper is the capability of a machine to overcome the asymmetrical fault.